2019
DOI: 10.1155/2019/2509242
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Diabetes Mellitus among Patients at Hawassa University Comprehensive Specialized Hospital, Hawassa, Southern Ethiopia

Abstract: Background. The burden of noncommunicable disease (NCD) in Africa is on a remarkable rise exacerbating the poor public health status affected by the existing but yet unsolved communicable disease. In Ethiopia, there is a paucity of evidence regarding prevalence and risk factors to NCD. Objective. This study sought to determine the prevalence of risk factors of NCDs, prevalence of DM and HTN, and risk factors associated with diabetes mellitus (DM) and hypertension (HTN). Method. This is an institution based cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 22 publications
(32 reference statements)
7
17
5
Order By: Relevance
“…No significant associations were found between hypertension and the marital status, education level, alcohol consumption or smoking habit factors in Uganda [14]. Previous studies have shown that smoking is associated with hypertension [8]. Interestingly, the rates for both smoking (2.5%) and alcohol consumption (0.33%) were low in our survey.…”
Section: Discussioncontrasting
confidence: 75%
See 4 more Smart Citations
“…No significant associations were found between hypertension and the marital status, education level, alcohol consumption or smoking habit factors in Uganda [14]. Previous studies have shown that smoking is associated with hypertension [8]. Interestingly, the rates for both smoking (2.5%) and alcohol consumption (0.33%) were low in our survey.…”
Section: Discussioncontrasting
confidence: 75%
“…Conversely, a lower rate (28.0%) of hypertension was reported in Tanzania [13] and in a population-based sectional study that enrolled 67,397 participants in Ethiopia (31.9%) [24]. In neighbouring Ethiopia, while a low rate (10.5%) of hypertension was reported in a hospital-based study [8], a prevalence rate of 34.7% for hypertension was reported in the capital, Addis Ababa [10]. In a metaanalysis of 43,025 older adults (> 53 years) in 15 African countries, it was reported that the overall pooled prevalence of hypertension was 57.0% (ranging from 22.3 to 90.0%) [25].…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations